Challenges of Arabic – English Translation - Zafar, Tojiyeva Zamira; Komilovich, Ermatov Usmonjon (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2024)
Arabic language is a rich language with a vast vocabulary, including terms that may not have direct equivalents in other languages. Translation is a field of contrastive linguistics since it is associated with at least two languages and their cultures. It is the process of conveying the text by transferring from one system of language to the other and often need to employ creative techniques to convey the richness of the original text in the translated version. In this article the focus will be on the problems of translating from Arabic language or into Arabic and will give several solutions.